(untitled) (Research, Society and Development, 2023)
Objective: To gather published information on cardiac complications in the context of post-COVID-19 infection. Methodology: This is an integrative review carried out in five phases, with the following research question: “What is the influence of cardiac pathologies in patients infected with COVID-19?”. This research included original scientific articles published between 2017 and 2022, written in English, Spanish or Portuguese and available in full. The search was performed in the Latin American and Caribbean Health Sciences Literature databases, Medical Literature Analysis and Retrieval System Online (MEDLINE) via PubMed, Web of Science and Scopus. Results: 875 articles were found, of which 32 were merged because they were duplicates; after reading the title and abstract of the remaining 843, 10 articles that fit for analysis were selected. All selected articles were published in English. Studies were conducted in Italy (30%), the United Kingdom (20%), the Netherlands (10%), Germany (10%), Egypt (10%), France (10%) and Sweden (10%). However, 6 articles have the research methodology as prospective cohort and 4 retrospective cohort. Conclusion: The outcome of COVID-19 infection is most often influenced by the prior presence of risk factors. However, people who do not have previous cardiac pathologies are less likely to develop cardiac complications.